2009
DOI: 10.1590/s0104-66322009000300006
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of 2-hydroxybenzoic acid by advanced oxidation processes

Abstract: -In this study, advanced oxidation processes (AOPs) such as the UV/H 2 O 2 and Fenton processes were investigated for the degradation of 2-hydroxybenzoic acid (2-HBA) in lab-scale experiments. Different [H 2 O 2 ]/[2-HBA] molar ratios and pH values were used in order to establish the most favorable experimental conditions for the Fenton process. For comparison purposes, degradation of 2-HBA was carried out by the UV/H 2 O 2 process under Fenton experimental conditions. The study showed that the Fenton process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…The aromatic hydroxylation of III results in the formation of dihydroxy benzoic acid (IV). These kind of compounds are reported as the major stable intermediates of hydroxy benzoic acids [49]. The decarboxylation reaction of this product will lead to the formation of dihydroxy phenol (V) followed by trihydroxy phenol (VI).…”
Section: Path 3 (Hydrolysis)mentioning
confidence: 99%
“…The aromatic hydroxylation of III results in the formation of dihydroxy benzoic acid (IV). These kind of compounds are reported as the major stable intermediates of hydroxy benzoic acids [49]. The decarboxylation reaction of this product will lead to the formation of dihydroxy phenol (V) followed by trihydroxy phenol (VI).…”
Section: Path 3 (Hydrolysis)mentioning
confidence: 99%
“…However, optimal pH values of around 7 have also been reported [17,33]. The inhibition of the Fenton process due to the influence of the pH might be explained by the following : (i) under an extremely low pH value (pH<2), the [Fe(H 2 O)] +2 formed reacts with H 2 O 2 , decreasing the production of OH • [34], (ii) the inhibition effect of the H + ions on OH • radicals assume higher importance under low pH values, (iii) Fe +3 and the H 2 O 2 reaction is inhibited under low pH conditions [35], (iv) at pH values higher than 4.5, the absence of H + inhibits the decomposition of the H 2 O 2 resulting in lower production of hydroxyl ions, (v) at pH values higher than 5, H 2 O 2 decomposes into water and oxygen; in addition, the formation of Fe complexes begins, deactivating the catalyzer [36], (vi) the oxidation potential of OH • decreases as the pH value increases. The H 2 O 2 amounts are a critical variable of the process, the OH • amount produced being directly dependent on it.…”
Section: Discussionmentioning
confidence: 99%
“…Higher degradation rates are usually observed at higher hydrogen peroxide concentrations due to reactive radical species (hydroxyl radicals) generation through H 2 O 2 molecules decomposition [23]. Studies have reported that at high doses the excess H 2 O 2 did not enhance the degradation rate, sometimes even inhibit the reaction [24]. The negative impact of excess H 2 O 2 on degradation rates can be related to its scavenging effects [25,26].…”
Section: Uv/h 2 Omentioning
confidence: 99%